(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
In today’s world, where the process of globalization is expanding and deepening on a global scale, the penetration of modern information and communication tools as well as digital technologies into all spheres of human life and their rapid development are causing significant changes in the development of society. The concepts of “Information Society” and “Digital Technologies” have acquired a global significance. These processes influence human thinking in various directions, affecting humanity’s life in different ways, sometimes positively and sometimes negatively, becoming a powerful force that shapes outcomes.